Evaluation of Childhood Psychosis Negligence: Cultural Influences in Treatment Process: Case Report - Royke Tony Kalalo; T, Maria; Tiwik Koesdiningsih; Justina Evy Tyaswati (Faculty of Medicine, Universitas Airlangga, 2022)
Background: Childhood psychosis is a rare condition. In Indonesia, strong cultural influences how people perceive mental disorders. Culture and knowledge interact dynamically in mental health in Indonesia. Lack of mental health knowledge, resulting abandonment among psychosis patients, especially in their first episode. This negligence leads to no medical treatment associated with a worse disease course. Case: 27 years old male with the third episode of psychosis. He presented with schizoaffective disorder mixed type. The earliest suspected psychosis episode was at the age of 12 years old, was not treated medically. The patient was only treated after his second episode of psychosis at the age of 26 but exhibited non-adherence to the treatment later, which caused a relapse. After discharged, the patient was currently in the stabilization phase for 5 months with oral antipsychotics and long-acting antipsychotic injections. Besides medical treatment, this patient also sought spiritual treatment from psychics and religious treatment. Discussion: The challenges related to the psychosocial aspects faced in this case are lack of knowledge, strong influences of cultural belief on the patient for the cause, and treatment-seeking for the illness, which needs regard for the treatment process. Conclusion: Negligence of psychosis during childhood, which is not medically treated, could progress to worse episodes in later periods of life, but the protective factors influenced by culture are dynamism of belief related to the illness, endorsed multiple causations for the illness including natural and supernatural attribution, local wisdom to perceive a mental disorder, including in this case cultural-psychological concept.